Effect of single-layer graphene incorporation on TiO₂ photoanodes for enhanced photovoltaic performance of chlorophyll-based dye-sensitized solar cells - Uzfi Helmi Zamzami; Prihanto Trihutomo; Aminnudin Aminnudin; Tuan Amran Tuan Abdullah (Center of Biomass & Renewable Energy (CBIORE), 2026)
The increasing demand for renewable energy technologies has encouraged extensive research on dye-sensitized solar cells (DSSCs) utilizing environmentally friendly and sustainable conductive materials. This study aims to synthesize and characterize TiO₂/single-layer graphene composites as photoanodes to improve electron transport and photovoltaic performance in chlorophyll-based DSSCs. TiO₂/single-layer graphene composites were prepared with graphene concentrations of 0.5%, 1.0%, and 1.5% v/v, while pure TiO₂ was used as the control sample. The synthesized composites were deposited onto FTO substrates as photoanode films, and their structural, morphological, chemical, and optical properties were analyzed using XRD, SEM, FTIR, and UV–Vis spectroscopy. The photovoltaic performance of the fabricated DSSCs was evaluated through current–voltage (I–V) measurements. The results demonstrate that incorporation of single-layer graphene significantly improves crystallinity, surface homogeneity, and interfacial interaction between TiO₂ and graphene, as confirmed by the formation of Ti–O–C bonding. UV–Vis analysis revealed enhanced visible-light absorption, a redshift in the absorption edge, and reduced optical band gap energy after graphene incorporation, indicating improved light-harvesting capability. Among all investigated compositions, the TiO₂/single-layer graphene photoanode containing 1.0% v/v graphene exhibited the highest photovoltaic performance, achieving a power conversion efficiency of 1.09% with a fill factor of 63.7%. However, excessive graphene incorporation at 1.5% v/v caused particle agglomeration and reduced film uniformity, which negatively affected DSSC performance. Overall, moderate incorporation of single-layer graphene effectively enhanced conductivity, charge transport, and photovoltaic properties, highlighting its strong potential as an environmentally friendly conductive material for sustainable chlorophyll-based DSSC applications.